OFR-37-79 Investigation Of Color And Color Infrared Aerial Photographic Techniques For Mining And Reclamation Planning And Monitoring - William M. Knuth (The National Institute for Occupational Safety and Health (NIOSH), 1978)
The objectives of this study were the evaluation of the technical and economical feasibility of utilizing color and color infrared aerial photography to satisfy some informational needs for pre-mine planning, mine progress monitoring, and reclamation monitoring. Seven aerial data collection missions were conducted within a two year period over strip mine sites in Pennsylvania. Scales of 1:6,000; 1:12,000; 1:24,000; and 1:48,000 were flown on the first aerial mission. The 1:12,000 was chosen as the optimal scale for the remaining six flights. An extensive literature and legislative review and discussions with strip mine operators identified the informational parameters that could possibly be obtained from aerial photography. Interpretability accuracies were evaluated for parameters in the broad categories of land use, soils, water, vegetation, and geology. Seasonal interpretation characteristics were noted for infrared photography. Man hours for photointerpretation and costs of aerial data collection were monitored closely and incorporated into a cost benefit analysis. Those parameters that could be mapped, identified, or measured with accuracies =75 percent were incorporated into a photointerpretation training manual. An additional analysis was performed to determine the applicability of the interpretation methodologies and results developed for Eastern sites to Western surface coal mining sites. In addition, a separate aerial photographic interpretation manual was produced during this contract. It is intended to be utilized by eastern and midwestern surface mine operators and regulatory personnel.